The Popularity of Strict Churches - Tamney, Joseph B. (Review of religious research, 1998)
After briefly reviewing Kelley's ideal-church model, and relevant aspects of modernization theory, we set forth hypotheses about who favors church strictness, an essential aspect of Kelley's model. Data came from a sample of "Middletown" residents (N = 567). It was necessary to distinguish strictness and authoritativeness. While respondents did not believe church strictness is important, authoritative preachers were highly favored. Regression analyses showed that strictness was somewhat more important to the less educated. Authoritativeness was mainly valued by fundamentalists, and to a lesser extent by authoritarians and political conservatives. We conclude with a discussion of how the relative appeal of strictness and authoritativeness can be understood in terms of the current stage of modernity.